Nickel-coated copper slurry composition, nickel-coated copper slurry, electrode and photovoltaic heterojunction battery
By combining nickel-covered copper powder and conductive polymer resin in the nickel-covered copper paste composition, the problem of difficult balance between cost and conductivity in the prior art is solved, and the conductive performance and cost reduction of nickel-covered copper paste are improved. , suitable for efficient photovoltaic heterojunction batteries.
Patent Information
- Application Number
- CN202310354085.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-04
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-04-04
AI Technical Summary
The existing heterojunction battery paste is difficult to balance between cost and conductivity. Silver paste costs the highest, and the price of silver-clad copper paste is still high. The copper paste is prone to oxidation and leads to a decrease in electrical properties, which affects industrialization. In addition, polymer resins are Shrinkage during curing affects the conductive network.
Using nickel-covered copper paste compositions, including nickel-covered copper powder, conductive polymer resin and additives, through a combination of specific proportions, improve conductivity and oxidation resistance, reduce costs, form conductive network channels, and improve adhesion and conductivity. performance.
The conductive performance of nickel-clad copper-clad paste is improved, the oxidation resistance is enhanced, and the cost is reduced, and the electrode resistivity and resistance change rate are reduced. Photovoltaic heterojunction batteries have both low resistivity and low cost.
Smart Images

Figure BDA0004162971580000121 
Figure BDA0004162971580000141 
Figure BDA0004162971580000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a nickel-coated copper slurry composition, a nickel-coated copper slurry comprising the nickel-coated copper slurry composition or a nickel-coated copper slurry prepared from the nickel-coated copper slurry composition, an electrode and a photovoltaic heterojunction battery. Background Art
[0002] HJT battery, or amorphous silicon thin film heterojunction battery, is a heterojunction composed of two different semiconductor materials. HJT is the deposition of amorphous silicon thin film on crystalline silicon. It combines the advantages of crystalline silicon battery and thin film battery, with high conversion efficiency, low process temperature, low attenuation rate, double-sided power generation, simplified equipment process flow, large room for cost reduction and efficiency improvement, broad prospects, and is the development direction of the new generation of battery technology.
[0003] At present, heterojunction pastes on the market are mainly divided into silver paste, silver-coated copper paste, and copper paste. Among them, silver paste has a simple process, the best electrical properties and stability, and is the most mature mass production solution in the current market, but the cost of silver paste is the highest. The conductivity and various properties of silver-coated copper paste are close to those of silver paste, and the cost is better than pure silver paste. It is the main technical solution to reduce costs in the current market. However, the density of silver coating on the surface of copper powder, the easy oxidation of copper, and the continuous reduction of silver will cause the coating layer to become thinner, which will bring about the problem of reduced reliability risk. In addition, the price of silver-coated copper paste is still high, and the demand for cost reduction is still urgent. Copper paste has the lowest cost, and copper is the metal with the second highest conductivity after silver, but copper is easily oxidized, resulting in a decrease in electrical properties. This is an important reason why copper paste has not been industrialized in this field.
[0004] In addition, existing heterojunction low-temperature slurries generally use polymer resins as the bonding phase. The resin shrinks during the curing process, reducing the distance between the powders to form a conductive network. At the same time, the polymer resin coats the powders and wets the substrate to produce good adhesion. However, too good coating of the powder by the resin will also affect the conductivity of the slurry. Therefore, the adhesion and conductivity of the slurry need to be better balanced.
[0005] Therefore, it is very important to invent a photovoltaic heterojunction cell that has both lower resistivity and lower cost. Summary of the invention
[0006] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art, and to provide a nickel-coated copper slurry composition, a nickel-coated copper slurry including the nickel-coated copper slurry composition or prepared from the nickel-coated copper slurry composition, an electrode and a photovoltaic heterojunction battery. The nickel-coated copper slurry composition of the present invention includes nickel-coated copper powder and a conductive polymer resin, which can improve conductivity and reduce costs; the nickel-coated copper slurry including the nickel-coated copper slurry composition or prepared from the nickel-coated copper slurry composition of the present invention has better conductivity, higher oxidation resistance and lower cost, and has better industrialization prospects; the electrode prepared from the nickel-coated copper slurry of the present invention has lower resistivity and lower cost; the photovoltaic heterojunction battery including the electrode of the present invention has the characteristics of lower resistivity and lower cost.
[0007] A first aspect of the present invention provides a nickel-coated copper slurry composition, which comprises nickel-coated copper powder, a conductive polymer resin and an additive, wherein, based on 100 parts by weight of the nickel-coated copper slurry composition, the nickel-coated copper powder is 80-93 parts by weight, the conductive polymer resin is 2-15 parts by weight, and the additive is 2-10 parts by weight.
[0008] In one example, the weight ratio of the nickel-coated copper powder to the conductive polymer resin is (6-30):1.
[0009] In one example, the nickel-coated copper powder is a spherical powder, and the average particle size of the nickel-coated copper powder is 1-3 μm.
[0010] In one embodiment, the tap density of the nickel-coated copper powder is 2-5 g / cm 2 .
[0011] In one example, based on the total weight of the nickel-clad copper powder, the weight content of the nickel element is 5-30 wt %.
[0012] In one example, the conductive polymer resin is selected from one or more of polypyrrole, polythiophene, polyaniline and polyphenylene vinylene.
[0013] In one example, the auxiliary agent includes an organic binder, an organic solvent and a curing agent.
[0014] In one example, the organic binder is selected from one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, phenolic resin, phenolic epoxy resin and hydrogenated epoxy resin.
[0015] In one example, the organic solvent is selected from one or more of diethylene glycol butyl ether acetate, 1,4-butanediol diglycidyl ether, diformate and terpineol.
[0016] In one example, the curing agent is selected from one or more of hexafluoroantimonate cationic curing agent, ultrafine dicyandiamide, diaminodiphenyl sulfone and boron trifluoride-amine complex.
[0017] In one example, based on 100 weight parts of the nickel-copper paste composition, the organic binder is 1-5 weight parts, the organic solvent is 0.5-5 weight parts, and the curing agent is 0.1-0.5 weight parts.
[0018] In one example, based on 100 parts by weight of the nickel-coated copper paste composition, the nickel-coated copper powder is 85-90 parts by weight, the conductive polymer resin is 5-10 parts by weight, and the auxiliary agent is 4-8 parts by weight.
[0019] A second aspect of the present invention provides a nickel-coated copper slurry, which includes the nickel-coated copper slurry composition described in the first aspect or is prepared from the nickel-coated copper slurry composition.
[0020] In one example, the resistivity of the nickel-coated copper paste is lower than 10 uΩ·cm.
[0021] In one example, the resistance change rate of the nickel-coated copper paste is less than 10%.
[0022] The third aspect of the present invention provides an electrode, which is prepared from the nickel-copper slurry described in the second aspect.
[0023] A fourth aspect of the present invention provides a photovoltaic heterojunction cell, wherein the photovoltaic heterojunction cell comprises the electrode described in the third aspect.
[0024] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:
[0025] (1) The nickel-coated copper slurry composition of the present invention includes nickel-coated copper powder and a conductive polymer resin, which can improve conductivity and reduce costs;
[0026] (2) The nickel-coated copper slurry of the present invention has good electrical conductivity;
[0027] (3) The nickel-coated copper slurry of the present invention has high oxidation resistance;
[0028] (4) The nickel-coated copper slurry of the present invention has low cost;
[0029] (5) The electrode of the present invention has low resistivity and low resistance change rate;
[0030] (6) The electrode cost of the present invention is low;
[0031] (7) The photovoltaic heterojunction cell of the present invention has low resistivity and low resistance change rate;
[0032] (8) The photovoltaic heterojunction cell of the present invention has low cost.
[0033] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0034] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0035] A first aspect of the present invention provides a nickel-coated copper slurry composition, which comprises nickel-coated copper powder, a conductive polymer resin and an additive, wherein, based on 100 parts by weight of the nickel-coated copper slurry composition, the nickel-coated copper powder is 80-93 parts by weight, the conductive polymer resin is 2-15 parts by weight, and the additive is 2-10 parts by weight.
[0036] In the present invention, by introducing nickel-coated copper powder and conductive polymer resin into the nickel-coated copper paste composition, the nickel-coated copper paste comprising the nickel-coated copper paste composition or the nickel-coated copper paste prepared from the nickel-coated copper paste composition can achieve better conductivity, higher oxidation resistance and lower cost than the prior art. In order to further improve the effect, one or more technical features can be further optimized.
[0037] The nickel-coated copper slurry composition may include nickel-coated copper powder, a conductive polymer resin and an additive. The coating of the nickel layer in the nickel-coated copper powder is denser and more uniform than the coating of the silver-coated copper in the prior art, thereby improving the oxidation resistance of the nickel-coated copper slurry and reducing the cost of the nickel-coated copper slurry. At the same time, the conductive polymer resin is introduced into the nickel-coated copper slurry composition, so that the nickel-coated copper slurry can form a conductive network channel after curing, thereby improving the conductivity of the nickel-coated copper slurry, and achieving the effect that the nickel-coated copper slurry has good conductivity, high oxidation resistance and low cost.
[0038] Based on 100 parts by weight of the nickel-coated copper slurry composition, the nickel-coated copper powder is 80-93 parts by weight (for example, 80 parts by weight, 81 parts by weight, 82 parts by weight, 83 parts by weight, 84 parts by weight, 85 parts by weight, 86 parts by weight, 87 parts by weight, 88 parts by weight, 89 parts by weight, 90 parts by weight, 91 parts by weight, 92 parts by weight, and 93 parts by weight), the conductive polymer resin is 2-15 parts by weight (for example, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, and 15 parts by weight), and the auxiliary agent is 2-10 parts by weight (for example, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, and 10 parts by weight).
[0039] In one example, based on 100 parts by weight of the nickel-coated copper paste composition, the nickel-coated copper powder is 85-90 parts by weight, the conductive polymer resin is 5-10 parts by weight, and the auxiliary agent is 4-8 parts by weight.
[0040] In one example, the weight ratio of the nickel-coated copper powder to the weight ratio of the conductive polymer resin is (6-30):1 (for example, 6:1, 10:1, 15:1, 20:1, 25:1, 30:1). In the nickel-coated copper paste composition, increasing the relative amount of the conductive polymer resin can improve the conductive performance of the nickel-coated copper paste. Therefore, by limiting the weight ratio of the nickel-coated copper powder to the conductive polymer resin within this specific range, the purpose of balancing the conductive performance and reducing the cost can be achieved, so that the nickel-coated copper paste has the characteristics of good conductive performance and low cost.
[0041] In one example, the weight ratio of the nickel-coated copper powder to the conductive polymer resin is (8.5-18):1.
[0042] In one example, the nickel-coated copper powder is spherical powder.
[0043] In one example, the average particle size of the nickel-coated copper powder is 1-3 μm (eg, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm). The average particle size can be measured using a laser particle size analyzer.
[0044] In one example, the nickel-coated copper powder has an average particle size of 2-2.5 μm.
[0045] According to a specific embodiment, the tap density of the nickel-coated copper powder is 2-5 g / cm 2 (For example, 2g / cm 2 , 2.5g / cm 2 , 3g / cm2 , 3.5g / cm 2 , 4g / cm 2 , 4.5g / cm 2 , 5g / cm 2 ).
[0046] In one embodiment, the tap density of the nickel-coated copper powder is 2.5-3 g / cm 2 .
[0047] According to a specific embodiment, based on the total weight of the nickel-clad copper powder, the weight content of the nickel element is 5-30wt% (for example, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%). By limiting the weight content of the nickel element in the nickel-clad copper powder, the coating of the copper powder surface can be improved, thereby improving the oxidation resistance while meeting the resistance requirements.
[0048] In one example, based on the total weight of the nickel-clad copper powder, the weight content of the nickel element is 10-20 wt %.
[0049] In the present invention, the conductive polymer resin has conductivity. The conductive polymer resin can be used as a binder to coat the powder in the nickel-coated copper paste to wet the substrate and generate adhesion, and can also be used as a conductive agent to form a conductive network to improve the conductivity of the nickel-coated copper paste.
[0050] In one example, the conductive polymer resin can be selected from one or more of polypyrrole, polythiophene, polyaniline and polyphenylene vinylene.
[0051] In one example, the conductive polymer resin is polypyrrole.
[0052] In one example, the auxiliary agent includes an organic binder, an organic solvent and a curing agent.
[0053] In the present invention, the organic binder as a binder phase can also coat the powder and wet the substrate to generate adhesion. Therefore, the organic binder cooperates with the conductive polymer resin to further enhance the adhesion of the nickel-copper paste.
[0054] According to a specific embodiment, based on 100 weight parts of the nickel-copper slurry composition, the organic binder is 1-5 weight parts (eg, 1 weight part, 2 weight parts, 3 weight parts, 4 weight parts, 5 weight parts).
[0055] In one example, based on 100 weight parts of the nickel-copper paste composition, the organic binder is 2-4 weight parts.
[0056] In one example, the organic binder is selected from one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, phenolic resin, phenolic epoxy resin and hydrogenated epoxy resin.
[0057] According to a specific embodiment, based on 100 weight parts of the nickel-copper slurry composition, the organic solvent is 0.5-5 weight parts (for example, 0.5 weight parts, 1 weight parts, 1.5 weight parts, 2 weight parts, 2.5 weight parts, 3 weight parts, 3.5 weight parts, 4 weight parts, 4.5 weight parts, 5 weight parts).
[0058] In one example, based on 100 weight parts of the nickel-copper paste composition, the organic solvent is 1-2 weight parts.
[0059] In one example, the organic solvent is selected from one or more of diethylene glycol butyl ether acetate, 1,4-butanediol diglycidyl ether, diformate and terpineol.
[0060] According to a specific embodiment, based on 100 weight parts of the nickel-copper slurry composition, the curing agent is 0.1-0.5 weight parts (for example, 0.1 weight parts, 0.2 weight parts, 0.3 weight parts, 0.4 weight parts, 0.5 weight parts).
[0061] In one example, based on 100 weight parts of the nickel-copper paste composition, the curing agent is 0.2-0.4 weight parts.
[0062] In one example, the curing agent is selected from one or more of hexafluoroantimonate cationic curing agent, ultrafine dicyandiamide, diaminodiphenyl sulfone and boron trifluoride-amine complex.
[0063] In one example, the nickel-coated copper paste composition includes 80-93 parts by weight of the nickel-coated copper powder, 2-15 parts by weight of the conductive polymer resin, 1-5 parts by weight of the organic binder, 0.5-5 parts by weight of the organic solvent, and 0.1-0.5 parts by weight of the curing agent.
[0064] The components in the nickel-clad copper slurry composition of the present invention are formulated in specific proportions so that the conductive properties of the nickel-clad copper slurry comprising the nickel-clad copper slurry composition or the nickel-clad copper slurry prepared from the nickel-clad copper slurry composition can meet the requirements of the electrode for the nickel-clad copper slurry, thereby achieving the effect of balancing conductive properties and reducing costs.
[0065] In one example, the nickel-coated copper paste composition includes 85-90 parts by weight of the nickel-coated copper powder, 5-10 parts by weight of the conductive polymer resin, 2-4 parts by weight of the organic binder, 1-2 parts by weight of the organic solvent, and 0.2-0.4 parts by weight of the curing agent.
[0066] A second aspect of the present invention provides a nickel-coated copper slurry, which includes the nickel-coated copper slurry composition described in the first aspect or is prepared from the nickel-coated copper slurry composition.
[0067] The nickel-coated copper slurry can be prepared by a conventional preparation process.
[0068] The nickel-coated copper slurry can be applied to an electrode. The electrode requires that the resistivity of the nickel-coated copper slurry is lower than 10uΩ·cm (for example, 9.5uΩ·cm, 9uΩ·cm, 8uΩ·cm, 7uΩ·cm, 6uΩ·cm, 5uΩ·cm, 4uΩ·cm, 3uΩ·cm, 2uΩ·cm, 1uΩ·cm), and / or the resistance change rate of the nickel-coated copper slurry is lower than 10% (for example, 9.5%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5%).
[0069] When the resistivity and / or resistance change rate of the nickel-coated copper slurry is controlled within a certain range, the conductivity of the nickel-coated copper slurry can be improved and the cost can be reduced. When the resistivity of the nickel-coated copper slurry is higher than 10uΩ·cm, the power loss of the electrode is high, affecting the battery conversion efficiency. When the resistance change rate of the nickel-coated copper slurry is higher than 10%, the oxidation resistance of the electrode is low.
[0070] In one example, the resistivity of the nickel-coated copper paste is lower than 8 uΩ·cm.
[0071] In one example, the resistance change rate of the nickel-coated copper paste is less than 8%.
[0072] The nickel-clad copper slurry of the present invention includes the nickel-clad copper slurry composition of the present invention or is prepared from the nickel-clad copper slurry composition, and the resistivity and / or resistance change rate of the nickel-clad copper slurry is controlled within a certain range, so that the nickel-clad copper slurry meets the conductivity requirements of the electrode.
[0073] The third aspect of the present invention provides an electrode, which is prepared from the nickel-copper slurry described in the second aspect.
[0074] The material and structure of the electrode nickel removal copper coating slurry can be made according to the methods in the art, and can achieve the effects of low resistivity, low resistance change rate and low cost.
[0075] Since the electrode of the present invention is prepared from the nickel-coated copper slurry of the present invention, the conductivity of the electrode is improved and the cost is reduced.
[0076] A fourth aspect of the present invention provides a photovoltaic heterojunction cell, wherein the photovoltaic heterojunction cell comprises the electrode described in the third aspect.
[0077] The materials and structures of the photovoltaic heterojunction cell other than the electrodes can be made in accordance with the methods in the art, and can achieve the effects of low resistivity, low resistance change rate and low cost.
[0078] Since the photovoltaic heterojunction cell of the present invention includes the electrode of the present invention, the conductivity of the photovoltaic heterojunction cell is improved and the cost is reduced.
[0079] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0080] The following examples are used to illustrate the nickel-copper paste composition of the present invention.
[0081] Example 1
[0082] Nickel-coated copper powder: 90 parts by weight, average particle size 2 μm, tap density 2.5 g / cm 2 , the weight content of nickel element is 10wt%;
[0083] Conductive polymer resin: 6 parts by weight of polypyrrole;
[0084] Additives: 2 parts by weight of organic binder (1 part by weight of phenolic resin, 1 part by weight of bisphenol A epoxy resin), 1.7 parts by weight of organic solvent (butyl acetate), and 0.3 parts by weight of curing agent (hexafluoroantimonate cationic curing agent).
[0085] Example 2 Group
[0086] This group of examples is used to illustrate the effects of changing the weight of the conductive polymer resin.
[0087] Example 2a
[0088] This example is carried out with reference to Example 1, except that the weight of the conductive polymer resin is adjusted to 10 parts, see Table 1 for details.
[0089] Example 2b
[0090] This example is carried out with reference to Example 1, except that the weight of the conductive polymer resin is adjusted to 3 parts, see Table 1 for details.
[0091] Example 2c
[0092] This example is carried out with reference to Example 1, except that the weight of the conductive polymer resin is adjusted to 15 parts, see Table 1 for details.
[0093] Example 3
[0094] This example is carried out with reference to Example 1, except that the conductive polymer resin is adjusted to polyaniline, as shown in Table 1.
[0095] Example 4 Group
[0096] This group of examples is used to illustrate the effects of changing the weight of nickel-coated copper powder.
[0097] Example 4a
[0098] This example is carried out with reference to Example 1, except that the weight of the nickel-coated copper powder is adjusted to 85 parts, see Table 1 for details.
[0099] Example 4b
[0100] This example is carried out with reference to Example 1, except that the weight of the nickel-coated copper powder is adjusted to 80 parts, as shown in Table 1 for details.
[0101] Example 5 Group
[0102] This group of examples is used to illustrate the effects of changing the weight content of nickel in nickel-clad copper powder.
[0103] Example 5a
[0104] This example is carried out with reference to Example 1, except that the weight content of nickel element in the nickel-clad copper powder is adjusted to 20 wt %, see Table 1 for details.
[0105] Example 5b
[0106] This example is carried out with reference to Example 1, except that the weight content of nickel element in the nickel-clad copper powder is adjusted to 5 wt %, see Table 1 for details.
[0107] Example 6
[0108] This example is carried out with reference to Example 1, except that the tap density of the nickel-coated copper powder is adjusted to 5 g / cm 2 , see Table 1 for details.
[0109] Example 7
[0110] This example is carried out with reference to Example 1, except that the average particle size of the nickel-coated copper powder is adjusted to 3 μm, see Table 1 for details.
[0111] Table 1
[0112]
[0113] Comparative Example 1
[0114] The process is carried out in accordance with Example 1, except that the conductive polymer resin is replaced with an organic binder in the same weight portion.
[0115] Comparative Example 2
[0116] The method is carried out in accordance with Comparative Example 1, except that the nickel-coated copper powder is replaced with the same weight of silver powder, and the average particle size of the silver powder is 2 μm and the tap density is 2.5 g / cm 2 The weight content of silver in the silver powder is 92wt%.
[0117] Comparative Example 3
[0118] The method is carried out in accordance with Comparative Example 1, except that the nickel-coated copper powder is replaced by the same weight portion of silver-coated copper powder, and the average particle size of the silver-coated copper powder is 2 μm, and the tap density is 2.5 g / cm 2 The weight content of silver in the silver-coated copper powder is 10wt%.
[0119] Preparation Example
[0120] The nickel-coated copper slurry composition of the embodiment and the comparative example was subjected to planetary stirring and three-roll grinding process to prepare nickel-coated copper slurry. The prepared nickel-coated copper slurry was printed with a 480 mesh screen with a screen opening of 23um, and the slurry was cured at 200°C for 7 minutes and cooled to room temperature.
[0121] Test Case
[0122] 1. Resistivity test
[0123] The multimeter tests the resistance R of the silver paste, and the 3D microscope tests the thickness h and width d of the silver paste. The resistivity is calculated using the formula P=R*S / L (S is the cross-sectional area of the silver wire, and L is the length of the silver wire).
[0124] 2. Resistance change rate test
[0125] Use a multimeter to test the initial resistance R0 and the resistance R1 after loop measurement.
[0126] Resistance change rate = (R1-R0) / R0*100%.
[0127] 3. Cost calculation
[0128] The metal prices are calculated based on the China Changjiang Metal Network on that day, with silver price at 5,300 yuan / kg, copper price at 68 yuan / kg and nickel price at 213 yuan / kg.
[0129] The obtained results are recorded in Table 2.
[0130] Table 2
[0131]
[0132]
[0133] It can be seen from Table 2 that the nickel-clad copper slurry in the embodiment has low resistivity, low resistance change rate and low cost, which means that the nickel-clad copper powder and the conductive polymer resin are introduced into the nickel-clad copper slurry composition, so that the nickel-clad copper slurry including the nickel-clad copper slurry composition or the nickel-clad copper slurry prepared from the nickel-clad copper slurry composition has good conductivity, high oxidation resistance and low cost.
[0134] By comparing Example 1 with Comparative Example 2 and Comparative Example 3, it can be seen that the cost of the nickel-clad copper slurry of the present invention is significantly reduced, while the resistivity and resistance change rate are low, indicating that the nickel-clad copper slurry of the present invention has good conductivity and antioxidant properties while the cost is significantly reduced.
[0135] By comparing Example 1 with Comparative Example 1, it can be seen that the conductivity of the nickel-copper slurry of the present invention is significantly improved, indicating that the introduction of the conductive polymer resin improves the conductivity of the nickel-copper slurry.
[0136] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A nickel-copper slurry composition, characterized in that: The nickel-coated copper paste composition is composed of nickel-coated copper powder, conductive polymer resin and additives, wherein, based on 100 parts by weight of the nickel-coated copper paste composition, the nickel-coated copper powder is 85 to 90 parts by weight, the conductive polymer resin is 5 to 10 parts by weight, and the additive is 4 to 8 parts by weight; The weight ratio of the nickel-coated copper powder to the weight of the conductive polymer resin is (6-30):1; the nickel-coated copper powder is a spherical powder, and the average particle size of the nickel-coated copper powder is 1-3 μm; the tap density of the nickel-coated copper powder is 2-5 g / cm 3 ; Based on the total weight of the nickel-clad copper powder, the weight content of the nickel element is 5 to 30wt%; The conductive polymer resin is selected from one or more of polypyrrole, polythiophene, polyaniline and polyphenylene vinylene; The auxiliary agent is composed of an organic binder, an organic solvent and a curing agent; The organic binder is selected from one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, phenolic resin and hydrogenated epoxy resin; The organic solvent is selected from one or more of diethylene glycol butyl ether acetate, 1,4-butanediol diglycidyl ether and terpineol; The curing agent is selected from one or more of hexafluoroantimonate cationic curing agent, ultrafine dicyandiamide, diaminodiphenyl sulfone and boron trifluoride-amine complex; Based on 100 weight parts of the nickel-copper paste composition, the organic binder is 1 to 5 weight parts, the organic solvent is 0.5 to 5 weight parts, and the curing agent is 0.1 to 0.5 weight parts.
2. A nickel-coated copper slurry, characterized in that: The nickel-coated copper slurry comprises the nickel-coated copper slurry composition according to claim 1 or is prepared from the nickel-coated copper slurry composition.
3. The nickel-coated copper slurry according to claim 2, wherein: The resistivity of the nickel-coated copper paste is lower than 10 uΩ·cm, and / or the resistance change rate of the nickel-coated copper paste is lower than 10%.
4. An electrode, characterized in that: The electrode is prepared from the nickel-copper slurry according to claim 2 or 3.
5. A photovoltaic heterojunction cell, characterized in that: The photovoltaic heterojunction cell comprises the electrode according to claim 4.
Citation Information
Patent Citations
Electrically conductive adhesives
US20190292418A1
